Antibiogram of Escherichia coli Isolated from different Hospitals Wastewater in Erbil City, Iraq - Aziz, Rana; Al-Zubaidy, Fawzi; Al-Mathkhury, Harith; Resul, Bahram; Musenga, John (Iraqi Journal of Science, 2023)
Three hospitals were chosen for the present (Maternity hospital, Raperin hospital and Rhizgari hospital) survey within Erbil city, 36 water samples were collected at regular monthly interval periods beginning at January to December 2012. Microbial analysis was done by selective medium and biochemical tests and the isolated bacteria from those hospitals were Eshcerichia coli, Acinetobacter lowffii, Klebsiella pneumoniae, Moraxilla spp., Salmonella Typhi, Citrbtobacter freundii, Vibrio fluvials, Acinetobacter haemolyticus, Weeksella zoohelcum, Pasteurella multicida, and Pseudomonas aeroginosa. E. coli isolates were subjected to antimicrobial susceptibility testing. In vitro activities of 10 different antibiotics against E. coli isolates were showed a high resistance rate observed against ampicillin (80%) while the lowest resistance was to pipercillin/ tazobactam (22%). A high proportion of the E. coli isolates from the three hospitals revealed resistance to more than one antibiotic.